The metabolism of adrenal 11beta-hydroxyprogesterone, 11keto-progesterone and 16alpha-hydroxyprogesterone by steroidogenic enzymes - Van Rooyen, Desmare (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.